Sintered ceramic material for industrial slurry pump and preparation method of sintered ceramic material

By using β-silicon carbide combined with α-silicon carbide sintered ceramic materials, combined with ferrosilicon chromium alloy powder and high-temperature sintering technology, the problem of decomposition of existing ceramic materials at high temperatures is solved, and the high strength and good corrosion resistance of ceramic parts are achieved.

CN119874371APending Publication Date: 2025-04-25XIANGYANG WU ER WU PUMP IND
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411822327.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing silicon nitride combined with silicon carbide ceramic materials decompose at high temperatures, resulting in limited sintering temperature, insufficient mechanical properties and corrosion resistance, and poor performance especially under high concentrations and strong alkali conditions.

Method used

β-silicon carbide combined with α-silicon carbide sintered ceramic material, by adding ferrosilicon chromium alloy powder and a reasonable carbon source to the slurry, using high-temperature sintering technology (1500-1700℃) and sintering aid, β-SiC ceramic parts with metal plasticity and diamond structure are formed.

Benefits of technology

The mechanical properties and corrosion resistance of ceramic parts are significantly improved, the porosity is reduced, the flexural strength is increased to 85-110MPa, and it shows excellent corrosion resistance under high concentration and strong alkali conditions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a sintered ceramic material for an industrial slurry pump and a preparation method of the sintered ceramic material. The sintered ceramic material comprises the following raw materials in parts by weight: 50-70 parts of alpha-silicon carbide particles; 5 to 14 parts of ferrosilicon chromium alloy powder; 0.2 to 1.5 parts of a binder; 4-10 parts of a carbon source; 5 to 10 parts of purified water; 0.2 to 2 parts of a dispersant; 0.1 to 1 part of a water reducing agent; 0.5 to 3 parts of a sintering aid; and 0.5 to 2 parts of a defoaming agent. The preparation method comprises the following steps: carrying out sufficient ball milling, wheel milling, kneading and ageing on mixed slurry to obtain homogeneous mixed slurry; injecting the slurry into a plaster mold for curing and molding, and demolding after drying to obtain a sintered ceramic green body. And embedding the green body into graphite in an argon / nitrogen atmosphere, carrying out stepped heating to 1500-1700 DEG C, carrying out heat preservation for 2-8 hours, and carrying out stepped cooling to room temperature so as to obtain a sintered ceramic product. The ceramic material prepared by adopting the formula and the method has the characteristics of high strength and low porosity, not only ensures the wear resistance of the ceramic pump, but also has good fracture toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a sintered ceramic material for an industrial slurry pump and a preparation method thereof, and more specifically to a sintered ceramic material of beta-silicon carbide combined with alpha-silicon carbide containing a metal plastic phase and a preparation method thereof, belonging to the technical field of sintered ceramic materials. Background Art

[0002] With the development of modern industry, the service environment of industrial slurry pumps has become harsh. Under the interaction of corrosion, erosion and cavitation, the service life of the metal flow parts of general industrial slurry pumps has been reduced, and the performance is difficult to meet the harsh working environment. Some industrial slurry pumps use sintered ceramic materials as pump body flow parts. At present, the commonly used sintered materials are silicon nitride combined with silicon carbide ceramics. Silicon carbide particles have the advantages of good wear resistance and corrosion resistance due to their high hardness and stable chemical structure. However, the silicon nitride (whiskers and small particles) generated by the reaction of elemental silicon and nitrogen in the silicon nitride combined with silicon carbide materials is not densely combined with the silicon carbide particles in the raw materials, resulting in the silicon nitride combined with silicon carbide being loose and not dense. In a nitrogen atmosphere, silicon nitride is above 1600°C and silicon nitride gradually decomposes. Therefore, the maximum sintering temperature is limited, resulting in the overall mechanical properties of the silicon nitride combined with silicon carbide samples being limited. Generally, the porosity of silicon nitride combined with silicon carbide is usually 15-18%, and the flexural strength is generally not more than 65MPa. In addition, the presence of silicon nitride significantly increases the degree of corrosion under the condition of high concentration of strong alkali (≥40%wt, NaOH solution). As a flow-through rotating part, it requires excellent mechanical properties and corrosion resistance, so it is imperative to reduce the porosity of ceramic parts and enhance their mechanical properties and corrosion resistance.

[0003] Lü Chunjiang et al. [1] compared the melting and alkali resistance of β-silicon carbide combined with α-silicon carbide and reaction-sintered silicon nitride combined with silicon carbide. It can be seen that the melting and alkali resistance of silicon carbide combined with silicon carbide is significantly better than that of silicon nitride combined with silicon carbide.

[0004] Hui-fang Wang et al. [2] sintered a ceramic material of β-silicon carbide combined with α-silicon carbide at 1400°C with a mechanical property of 59.33MPa. Based on this, the present invention adopts a sintering temperature of 1500-1700°C and adds ferrosilicon chromium alloy powder to sinter β-silicon carbide combined with α-silicon carbide.

[0005] Compared with silicon nitride combined with silicon carbide, β-silicon carbide combined with α-silicon carbide can be heated to 1500℃ to 1700℃, and the material is sintered more fully, which is beneficial to improve the mechanical properties;

[0006] On the basis of ensuring the construction performance and the strength of the green body, in the slurry ratio, the water reducer can be adsorbed on the surface of the silicon carbide particles. The long chains in the molecules extend into the water phase, and the agglomeration of the silicon carbide particles is reduced through spatial repulsion, thereby reducing the use of pure water. The porosity of the sintered ceramic parts is reduced to 7%-12%, which improves the mechanical properties of the ceramics.

[0007] During sintering, the silicon in the ceramic sample is completely reacted when buried in graphite, and the residual chromium-iron alloy combines with the β-SiC generated by the high-temperature reaction, making the ceramic part have metallic plasticity and good mechanical properties. At the same time, there is no silicon infiltration residue, and it also has good corrosion resistance under high-concentration strong alkali conditions.

[0008] During the sintering process of ceramic parts, there are problems such as residual SiO2. The introduction of ferrosilicon-chromium alloy powder can reduce SiO2 and promote the growth of SiC whiskers while ensuring the amount of SiC generated.

[0009] Mass fraction ratio of sintering aid active lanthanum oxide micropowder and active zirconium oxide micropowder (10-30%):

[0010] (70-90%), which makes the sintered ceramic sample denser without producing too much liquid phase, thereby improving the mechanical properties of the sintered ceramic sample.

[0011] During the reaction sintering process, the expansion coefficient of silicon carbide generated by the reaction of graphite and silicon is greater than the expansion coefficient of silicon carbide generated by carbon black. When a reasonable carbon source mass fraction ratio (the mass fraction ratio of carbon black, graphite, and chopped short fibers is (25-40%): (35-60%): (15-20%)) is used, while ensuring that the sintered ceramic parts do not crack, the pores of the sintered ceramic parts are filled to the maximum extent. At the same time, the newly formed β-SiC adheres to the chopped carbon fibers and forms a skeleton structure together with the chopped carbon fibers, which significantly improves the mechanical properties of the sintered ceramic parts.

[0012] The β-SiC formed by reaction sintering is a low-temperature modified phase with a diamond structure, which improves the wear resistance of reaction-sintered ceramic parts and has excellent corrosion resistance under strong alkaline conditions. Summary of the invention

[0013] The purpose of the present invention is to provide a sintered ceramic material for an industrial slurry pump and a preparation method thereof, so as to achieve the characteristics of high strength and low porosity of the ceramic material, thereby ensuring the wear resistance of the ceramic pump and having good fracture toughness.

[0014] The objective of the present invention is achieved through the following technical solutions:

[0015] The present invention discloses a sintered ceramic material for an industrial slurry pump. The sintered ceramic material slurry comprises 50-70 parts by weight of α-silicon carbide particles, 5-14 parts by weight of ferrosilicon chromium alloy powder, 0.2-1.5 parts by weight of a binder, 4-10 parts by weight of a carbon source, 5-10 parts by weight of pure water, 0.2-2 parts by weight of a dispersant, 0.1-1 parts by weight of a water reducer, 0.5-3 parts by weight of a sintering aid, and 0.5-2 parts by weight of a defoaming agent.

[0016] The α-silicon carbide particles are mixed by 12-20 mesh, 20-36 mesh, 36-70 mesh, 70-100 mesh, 100-150 mesh, 150-200 mesh, and particle sizes greater than 200 mesh according to the mass ratio of (0-50%): (0-25%): (5-20%): (5-20%): (5-15%): (25-60%), and the density of the α-silicon carbide particles is greater than 98%.

[0017] The ferrosilicon-chromium alloy powder is a mixture of silicon, iron and chromium in a mass ratio of (55-75%): (5-10%): (5-15%); the particle size of the ferrosilicon-chromium alloy powder is 10-88 μm, and the purity is ≥99.8%.

[0018] The adhesive is a composite of one or more of water-soluble phenolic resin, gum arabic, sodium hydroxymethyl cellulose and sodium carboxymethyl cellulose.

[0019] The carbon source is a mixture of carbon black, graphite and chopped carbon fibers in a mass fraction ratio of (25-40%): (35-60%): (15-20%); the particle size of the carbon black is 200-500nm; the particle size of the graphite is less than 45μm; the length of the chopped carbon fibers is 0.1-7mm and the diameter is 5-70μm.

[0020] The dispersant is prepared by mixing polyvinyl pyrrolidone K30 or K90, polyethylene glycol and polyvinyl alcohol in a mass fraction ratio of (30-100%): (0-40%): (0-40%).

[0021] The water reducing agent is polyhydroxy acid.

[0022] The sintering aid is formed by mixing active lanthanum oxide micropowder and active zirconium oxide micropowder in a mass fraction ratio of (10-30%): (70-90%), and the particle size of the sintering aid is 1-74 μm.

[0023] The selected defoaming agent is a mixture of one or more of diethylhexanol, isooctyl alcohol, isopentanol and diisobutyl carbinol.

[0024] The present invention provides a method for preparing a sintered ceramic material for an industrial slurry pump, and the specific preparation steps are as follows:

[0025] 1) The ingredients are prepared according to the above formula ratio. First, the fixed particles with a particle size of ≤88 μm in the formula are ball-milled at a speed of 80-120 r / min for 1-48 hours; then the fixed particles with a particle size of >88 μm in the formula are added, and the particles are wheel-milled at a speed of 10-50 r / min for 2-12 hours; then the liquid material in the formula is added, and the mixture is kneaded at a kneading speed of 50-350 r / min for 1-5 hours to obtain a uniformly distributed mixed slurry, and then the material is trapped for 10-48 hours;

[0026] 2) injecting the mixed slurry obtained in step 1) into a mold, allowing it to stand for more than 0.5 h to completely replenish the lowered liquid level, and allowing it to cure at room temperature for 1-2 days to obtain a formed ceramic part;

[0027] 3) drying the formed ceramic part obtained in step 2) at 50-180° C. for 1-7 days, and obtaining a solidified ceramic body after demolding;

[0028] 4) The ceramic body obtained in step 3) is buried in expanded graphite, and in a high-purity argon / nitrogen environment, the temperature is increased to 800±30°C at 3-10°C / min, and the temperature is kept for 0.5-2h; then the temperature is increased to 1500-1700°C at 3-5°C / min, and the temperature is kept for 2-8h; then the temperature is decreased to 800-1000°C at 3-5°C / min, and finally the temperature is cooled to room temperature with the furnace to obtain a sintered ceramic product.

[0029] Beneficial Effects

[0030] 1. In the slurry ratio, the use of water reducer reduces the water content, and the porosity of the sintered ceramic parts drops to 7-12%, which improves the mechanical properties of the ceramics. 2. The sintering temperature of the material can reach up to 1500℃ to 1700℃, so that part of α-silicon carbide is converted into β-silicon carbide to form a mixed crystal form. Compared with silicon nitride combined with silicon carbide, not only is the sintering of the material more complete, but it is also more conducive to improving the mechanical properties; 3. The high-temperature reaction generates β-SiC combined with the metal alloy mesh that has not been completely reacted in the raw material, which improves the mechanical properties of the ceramic parts and the flexural strength reaches 85 to 110MPa. 4. During the reaction sintering process, the expansion rate of silicon carbide generated by the reaction of graphite and silicon is greater than the expansion rate of silicon carbide generated by carbon black. When a reasonable carbon source mass ratio is used (the mass fraction ratio of carbon black, graphite, and chopped short fibers is (25-40%): (35-60%): (15-20%)), while ensuring that the sintered ceramic parts do not crack, the pores of the sintered ceramic parts are filled to the maximum extent. At the same time, the newly formed β-SiC adheres to the chopped carbon fibers and forms a skeleton structure together with the chopped carbon fibers, which significantly improves the mechanical properties of the sintered ceramic parts. 5. The mass fraction ratio of the sintering aids activated lanthanum oxide micropowder and activated zirconium oxide micropowder is (10-30%): (70-90%), which makes the sintered ceramic samples denser without producing too much liquid phase, thereby improving the mechanical properties of the sintered ceramic samples. 6. The β-SiC formed by reaction sintering is a low-temperature modified phase with a diamond structure, which improves the wear resistance of reaction-sintered ceramic parts and has excellent corrosion resistance under strong alkaline conditions. DETAILED DESCRIPTION

[0031] The present invention will be further described below in conjunction with the embodiments.

[0032] Example 1

[0033] A method for preparing a sintered ceramic material for an industrial slurry pump, wherein the weight portions of each raw material in the 10kg composite ceramic material slurry are as follows: 3307g of silicon carbide particles with a mesh number of 12-20, 472g of silicon carbide particles with a mesh number of 20-36, 945g of silicon carbide particles with a mesh number of 36-70, 473g of silicon carbide particles with a mesh number of 70-100, 203g of silicon carbide particles with a mesh number of 100-150, 945g of silicon carbide particles with a mesh number of 150-200, and 945g of silicon carbide particles with a mesh number of >200. particles: 405g; ferrosilicon chromium alloy powder: 1200g; binder 100g; purified water 700g; carbon source: 800g (carbon black: 267g; graphite: 400; chopped carbon fiber: 133g); dispersant: 100g (polyvinyl pyrrolidone K90: 60g; polyethylene glycol: 20g; polyvinyl alcohol: 20g); water reducer: 50g (polycarboxylic acid: 100g); sintering aid: 100g (lanthanum oxide: 30g; zirconium oxide 70g); defoaming agent 100g (isooctanol: 100g).

[0034] Step 1, raw material mixing: firstly, mix the micro powder (particle size ≤ 88 μm), including ferrosilicon chromium alloy powder, carbon source, sintering aid, and silicon carbide particles of >200F mesh, and ball mill them at a speed of 80 r / min for 48 hours; then add coarse silicon carbide particles (particle size >88 μm), including silicon carbide particles of 12-20 mesh, 20-36 mesh, 36-70 mesh, 70-100 mesh, 100-150 mesh, and 150-200 mesh, and grind them at a wheel speed of 10 r / min for 12 hours, then add binder, defoamer, purified water and other liquids through a kneader at a kneading speed of 50 r / min, knead for 5 hours, and obtain a uniformly distributed mixture; trap the material for 48 hours;

[0035] Step 2, injection molding: inject the mixed slurry into the gypsum mold, let it stand for 0.5 hours, and after the mold is fully filled with the slurry, replenish the lowered liquid level completely, and place it at room temperature to cure for 1 day;

[0036] Step 3, heating and molding: placing the molded ceramic part in an oven and heating it to 50°C, and then demolding it after drying for 7 days to obtain a solidified ceramic body;

[0037] Step 4, high temperature sintering: the ceramic body is placed in a high-purity argon / nitrogen (argon purity / nitrogen>99.99%), and the sample is buried in expanded graphite, and the temperature is increased to 770°C at 3°C / min, and kept warm for 0.5h, and then increased to 1500°C at 3°C / min, and the holding time is 2h; after the heat treatment is completed, the sintering furnace is cooled to 770°C at a rate of 3°C / min, and then cooled to room temperature with the furnace to obtain a sintered ceramic part.

[0038] Example 2

[0039] A method for preparing a sintered ceramic material for an industrial slurry pump, wherein the weight portions of each raw material in the 10kg composite ceramic material slurry are as follows: 3307g of silicon carbide particles with a mesh number of 12-20, 472g of silicon carbide particles with a mesh number of 20-36, 945g of silicon carbide particles with a mesh number of 36-70, 473g of silicon carbide particles with a mesh number of 70-100, 203g of silicon carbide particles with a mesh number of 100-150, 945g of silicon carbide particles with a mesh number of 150-200, and 945g of silicon carbide particles with a mesh number of >200. particles: 405g; ferrosilicon chromium alloy powder: 1200g; binder 100g; purified water 700g; carbon source: 800g (carbon black: 228g; graphite: 343; chopped carbon fiber: 226g); dispersant: 100g (polyvinyl pyrrolidone K90: 60g; polyethylene glycol: 20g; polyvinyl alcohol: 20g); water reducer: 50g (polycarboxylic acid: 100g); sintering aid: 100g (lanthanum oxide: 30g; zirconium oxide 70g); defoaming agent: 100g (isooctanol: 100g).

[0040] Step 1, raw material mixing: firstly, mix the micro powder (particle size ≤ 88 μm), including ferrosilicon chromium alloy powder, carbon source, sintering aid, and silicon carbide particles of > 200 mesh, and ball mill at a speed of 100 r / min for 24 hours; then add coarse silicon carbide particles (particle size > 88 μm), including silicon carbide particles of 12-20 mesh, 20-36 mesh, 36-70 mesh, 70-100 mesh, 100-150 mesh, and 150-200 mesh, and grind them at a wheel speed of 30 r / min for 6 hours, then add binder, defoamer, purified water and other liquids through a kneader at a kneading speed of 200 r / min for 3 hours to obtain a uniformly distributed mixture; trap the material for 24 hours;

[0041] Step 2, injection molding: inject the mixed slurry into the gypsum mold, let it stand for 0.5 hours, and after the mold is fully filled with the slurry, replenish the lowered liquid level completely, and place it at room temperature to cure for 1.5 days;

[0042] Step 3, heating and molding: placing the molded ceramic part in an oven and heating it stepwise to 110°C, and then removing the mold after drying for 3 days to obtain a solidified ceramic body;

[0043] Step 4, high temperature sintering: the ceramic body is placed in a high-purity argon / nitrogen (argon purity / nitrogen>99.99%), and the sample is buried in expanded graphite, the temperature is increased to 800°C at 7°C / min, and the temperature is kept for 1h, and then the temperature is increased to 1600°C at 4°C / min, and the temperature is kept for 5h; after the heat treatment is completed, the sintering furnace is cooled to 900°C at a rate of 4°C / min, and then cooled to room temperature with the furnace to obtain a sintered ceramic part.

[0044] Example 3

[0045] A method for preparing a sintered ceramic material for an industrial slurry pump, wherein the weight portions of each raw material in 10 kg of the composite ceramic material slurry are as follows: 3307 g of silicon carbide particles with a mesh number of 12-20, 472 g of silicon carbide particles with a mesh number of 20-36, 945 g of silicon carbide particles with a mesh number of 36-70, 473 g of silicon carbide particles with a mesh number of 70-100, 203 g of silicon carbide particles with a mesh number of 100-150, 945 g of silicon carbide particles with a mesh number of 150-200, and 975 g of silicon carbide particles with a mesh number greater than 200. : 405g; ferrosilicon chromium alloy powder: 1150g; binder 100g; pure water 700g; carbon source: 800g (carbon black: 228g; graphite: 343; chopped carbon fiber: 226g); dispersant: 100g (polyvinyl pyrrolidone K90: 60g; polyethylene glycol: 20g; polyvinyl alcohol: 20g); water reducer: 100g (polycarboxylic acid: 100g); sintering aid: 100g (lanthanum oxide: 30g; zirconium oxide 70g); defoaming agent: 100g (isooctanol: 100g).

[0046] Step 1, raw material mixing: firstly, mix the micro powder (particle size ≤ 88 μm), including ferrosilicon chromium alloy powder, carbon source, sintering aid, and silicon carbide particles of > 200 mesh, mix, and ball mill at a speed of 120 r / min for 1 hour; then add coarse silicon carbide particles (particle size > 88 μm), including silicon carbide particles of 12-20 mesh, 20-36 mesh, 36-70 mesh, 70-100 mesh, 100-150 mesh, and 150-200 mesh, and grind them at a wheel speed of 50 r / min for 2 hours, then add binder, defoamer, purified water and other liquids through a kneader at a kneading speed of 350 r / min, knead for 1 hour, and obtain a uniformly distributed mixture; trap the material for 10 hours;

[0047] Step 2, injection molding: inject the mixed slurry into the gypsum mold, let it stand for 0.5 hours, and after the mold is fully filled with the slurry, replenish the lowered liquid level completely, and place it at room temperature to cure for 2 days;

[0048] Step 3, heating and molding: placing the molded ceramic part in an oven and step-wise heating it to 180°C, drying it for 1 day and then demolding it to obtain a solidified ceramic body;

[0049] Step 4, high temperature sintering: the ceramic body is placed in a high-purity argon / nitrogen (argon purity / nitrogen>99.99%), and the sample is buried in expanded graphite, the temperature is increased to 830°C at 10°C / min, and the temperature is kept for 2h, and then the temperature is increased to 1700°C at 5°C / min, and the holding time is 8h; after the heat treatment is completed, the sintering furnace is cooled down to 1000°C at 5°C / min, and then cooled to room temperature with the furnace to obtain a sintered ceramic part.

[0050] The performance indicators of the sintered ceramic products obtained in each embodiment are:

[0051] Example 1: porosity 8.4%; room temperature flexural strength 92.2MPa, room temperature wear resistance 0.134cm 2 , under the condition of strong alkali (40%wt, NaOH solution) at 100-200℃, the ceramic sample lost 0.002g, and there was no obvious change on the surface;

[0052] Example 2: porosity 8.9%; room temperature flexural strength 99.8MPa, room temperature wear resistance 0.135cm 2 , under the condition of strong alkali (40%wt, NaOH solution) at 100-200℃, the ceramic sample lost 0.008g, and there was no obvious change on the surface;

[0053] Example 3: porosity 7.5%; room temperature flexural strength 105.3MPa, room temperature wear resistance 0.135cm 2 , under the condition of strong alkali (40%wt, NaOH solution) at 100-200℃, the ceramic sample lost 0.006g, and there was no obvious change on the surface;

[0054] It can be seen from Examples 1, 2, and 3 that, on the basis of ensuring construction performance and green billet strength, the use of a water reducer reduces the use of pure water and a binder, and the porosity of the sintered ceramic parts will be reduced; the increase in chopped carbon fibers increases the room-temperature flexural strength of the sintered ceramic parts; the ferrosilicon-chromium alloy powder reacts with the carbon source without siliconizing residue, so that the sintered ceramic parts have better corrosion resistance under high-concentration strong alkali (40%wt, NaOH solution) conditions at 100-200°C, and the residual ferrochromium alloy makes the metal plastic and has good mechanical properties.

Claims

1. A sintered ceramic material for an industrial slurry pump, characterized in that: The sintered ceramic material slurry is calculated based on 100 parts by total weight, and the weight parts of the raw materials are: α-silicon carbide particles: 50-70 parts; ferrosilicon chromium alloy powder: 5-14 parts; binder: 0.2-1.5 parts; carbon source: 4-10 parts; Purified water: 5-10 parts; Dispersant: 0.2-2 parts; Water reducing agent: 0.1-1 part; burning aid: 0.5-3 parts; Defoaming agent: 0.5-2 parts; The α-silicon carbide particles are mixed with 12-20 mesh, 20-36 mesh, 36-70 mesh, 70-100 mesh, 100-150 mesh, 150-200 mesh, and particle sizes greater than 200 mesh according to the mass ratio of (0-50%): (0-25%): (5-20%): (5-20%): (5-15%): (25-60%); The ferrosilicon-chromium alloy powder is a mixture of silicon, iron and chromium in a mass ratio of (55-75%): (5-10%): (5-15%); the particle size of the ferrosilicon-chromium alloy powder is 10-88 μm; The adhesive is a composite of one or more of water-soluble phenolic resin, gum arabic, sodium hydroxymethyl cellulose and sodium carboxymethyl cellulose; The carbon source is a mixture of carbon black, graphite and chopped carbon fibers in a mass fraction ratio of (25-40%): (35-60%): (15-20%); the particle size of the carbon black is 200-500nm; the particle size of the graphite is less than 45μm; the length of the chopped carbon fibers is 0.1-7mm and the diameter is 5-70μm; The dispersant is a mixture of polyvinylpyrrolidone K30 or K90, polyethylene glycol and polyvinyl alcohol in a mass fraction ratio of (30-100%): (0-40%): (0-40%); The water reducing agent is polyhydroxy acid; The sintering aid is a mixture of active lanthanum oxide micropowder and active zirconium oxide micropowder in a mass fraction ratio of (10-30%): (70-90%), and the particle size of the sintering aid is 1-74 μm; The selected defoaming agent is a mixture of one or more of diethylhexanol, isooctyl alcohol, isopentanol and diisobutyl carbinol.

2. A sintered ceramic material for an industrial slurry pump according to claim 1, characterized in that: The density of the α-silicon carbide particles is greater than 98%.

3. A sintered ceramic material for an industrial slurry pump according to claim 1, characterized in that: The purity of the ferrosilicon-chromium alloy powder is ≥99.8%.

4. A method for preparing a sintered ceramic material for an industrial slurry pump, the specific preparation steps are as follows: 1) The ingredients are prepared according to the formula ratio of the sintered ceramic material as described in any one of claims 1 to 3, firstly, the fixed particles with a particle size of ≤88 μm in the formula are ball-milled at a speed of 80-120 r / min for 1-48 h; then, the fixed particles with a particle size of >88 μm in the formula are added, and the mixture is wheel-milled at a speed of 10-50 r / min for 2-12 h; then, the liquid material in the formula is added, and the mixture is kneaded at a kneading speed of 50-350 r / min for 1-5 h to obtain a uniformly distributed mixed slurry, and then the mixture is trapped for 10-48 h; 2) injecting the mixed slurry obtained in step 1) into a mold, allowing it to stand for more than 0.5 h to completely replenish the lowered liquid level, and allowing it to cure at room temperature for 1-2 days to obtain a formed ceramic part; 3) drying the formed ceramic part obtained in step 2) at 50-180° C. for 1-7 days, and obtaining a solidified ceramic body after demolding; 4) The ceramic body obtained in step 3) is buried in expanded graphite, and in a high-purity argon / nitrogen environment, the temperature is increased to 800±30°C at 3-10°C / min, and the temperature is kept for 0.5-2h; then the temperature is increased to 1500-1700°C at 3-5°C / min, and the temperature is kept for 2-8h; then the temperature is decreased to 800-1000°C at 3-5°C / min, and finally the temperature is cooled to room temperature with the furnace to obtain a sintered ceramic product.

Citation Information

Cited By

  • Zirconium oxide composite ceramic microbead and preparation method thereof

    CN120136545A

  • Porous infiltrating high-toughness ceramic material for industrial pump and preparation method of porous infiltrating high-toughness ceramic material

    CN121651980A